Trusted but isolated: how perceived trust from leaders leads to workplace exclusion through being the target of envy - Song, Linjia; Yao, Kai; Li, Lingyu (Frontiers in Psychology, 2025)
This study explores the unintended interpersonal consequences of perceived trust from leaders—a core element of inclusive leadership—within multicultural team settings. While leader trust is typically associated with positive outcomes, our research reveals its paradoxical role in fostering workplace exclusion. Drawing on social comparison theory and using a two-study design (a contextual experiment and a multi-source field survey), we examine how perceived trust from leaders can lead to being the target of envy among coworkers and trigger workplace exclusion behaviors. Furthermore, the perceived competitive climate amplifies these effects, highlighting the boundary conditions under which inclusive leadership practices may unintentionally harm team dynamics. The findings provide novel insights into the “dark side” of inclusive leadership, offering practical guidance for managing trust and team competitiveness in culturally diverse organizations. Robustness checks addressing stable individual differences yielded the same pattern of results.